Method for silk-screen printing of metallized paste

By homogenizing and defoaming the metallized paste and controlling the screen printing thickness, the problem of surface defects of the metallized layer in metal-ceramic sealing is solved, and the sealing quality and reliability are improved.

CN119874409AInactive Publication Date: 2025-04-25LEADING THIN FILM MATERIALS (JIANGSU) CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510144195.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-10
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In metal-ceramic sealing, the difference in thermal expansion coefficients between ceramics and metals leads to the influence of high temperature and temperature changes on the performance of the sealing part. Increasing the thickness of the metallization layer will lead to an increase in the silk screen thickness, which is prone to defects such as grooves and pits on the surface of the metallization paste layer, reducing the sealing quality and reliability.

Method used

The metallized paste is treated by homogenization and defoaming activation, and the thickness of the screen printing is controlled to be no more than 50 μm. By screen printing multiple times to a set thickness, combined with sintering treatment, a high-quality metallized layer is formed.

Benefits of technology

It effectively improves the surface condition of the metallization paste layer, avoids defects such as grooves and cracks, and improves the quality and reliability of metal-ceramic sealing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874409A_ABST
    Figure CN119874409A_ABST
Patent Text Reader

Abstract

The invention discloses a method for silk-screen printing of metallized paste, which comprises the following steps of: S1, sequentially homogenizing, defoaming and activating the metallized paste to obtain activated metallized paste; s2, performing silk-screen printing on the metalized paste activated in the step S1 on the to-be-sealed surface of a ceramic material, controlling the silk-screen printing thickness at each time to be not greater than 50 microns, and performing silk-screen printing for multiple times until the set thickness is reached, so as to obtain a ceramic material containing a metalized paste layer; and S3, sintering the ceramic material containing the metallized paste layer in the step S2 to obtain the ceramic material containing the metallized layer. According to the method disclosed by the invention, the defects of grooves, cracks and the like which are easy to appear on the surface of the metalized paste layer after silk-screen printing are avoided by controlling the thickness of silk-screen printing, so that the quality of metal-ceramic sealing is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic metallization, and in particular relates to a method for screen printing metallization paste. Background Art

[0002] Metal-ceramic sealing has a wide range of applications in electronics, electricity, aerospace, automobile manufacturing, medical devices, and new energy. Effective sealing between metal and ceramic is crucial to improving product performance and reliability, especially in some special application scenarios, such as fuel cells, aerospace engines, ion beam sources, and vacuum heating furnaces. These seals need to maintain stable performance at high temperatures and be able to withstand temperature shocks from high temperatures to room temperature. Therefore, higher requirements are placed on the quality of the metallization layer of the seal. Due to the large difference in the thermal expansion coefficients of ceramics and metals, in order to reduce the impact of high temperature and temperature changes on the performance of the seal, the thickness of the metallization layer of the seal is usually increased (generally between 25-50μm). However, the increase in the thickness of the metallization layer will lead to an increase in the screen printing thickness, which makes the screen-printed metallization paste layer prone to defects. In particular, when the size of the ceramic surface to be screen-printed in one direction is less than 5 mm and the screen printing thickness exceeds 50μm, defects such as grooves and pits are very likely to appear on the surface of the metallization paste layer, thereby reducing the quality and reliability of the metal-ceramic seal. Summary of the invention

[0003] The purpose of the present invention is to provide a method for screen printing a metallization paste, which can effectively improve the surface condition of the metallization paste layer and enhance the metal-ceramic sealing quality.

[0004] In a first aspect, the present invention provides a method for screen printing a metallization paste, which adopts the following technical solution: A method for screen printing a metallized paste comprises the following steps: Step S1: homogenizing and degassing the metallized paste in sequence to obtain an activated metallized paste; Step S2: screen-printing the metallized paste activated in step S1 on the surface of the ceramic material to be sealed, controlling the thickness of each screen printing to be no more than 50 μm, and performing multiple screen printing to a set thickness; obtaining a ceramic material containing a metallized paste layer; Step S3: sintering the ceramic material containing the metallization paste layer in step S2 to obtain a ceramic material containing the metallization layer.

[0005] Preferably, in step S1, homogenization is performed under vacuum conditions with a vacuum degree of -120 to -90 KPa.

[0006] Preferably, in step S1, the homogenization speed is 1200-1600 r / min, and the homogenization time is 10-15 min.

[0007] Preferably, in step (1), ultrasonic degassing is used for degassing.

[0008] Further preferably, the frequency of the ultrasonic degassing is 40-80 KHz, and the time of the ultrasonic degassing is 10-15 min.

[0009] Preferably, in step S2, the process parameters of screen printing include: screen mesh size of 80-350 meshes, wire diameter of 20-45 μm, and screen spacing of 2-4 mm.

[0010] Preferably, in step S2, the process parameters of screen printing include: a scraper angle of 45-85°, a downward stroke of 28-35 μm, and a printing speed of 30-100 mm / s.

[0011] Preferably, in step S2, the thickness of each screen printing is controlled to be 25-50 μm.

[0012] Preferably, in step S2, drying is performed after each screen printing; the drying temperature is 100-130°C.

[0013] Preferably, in step S2, the thickness is set to 55-110 μm.

[0014] Preferably, in step S3, the sintering temperature is 1400-1600° C., and the sintering holding time is 0.5-1.5 h.

[0015] Beneficial effects of the present invention: (1) In the method of the present invention, by controlling the thickness of screen printing, defects such as grooves and cracks are avoided on the surface of the metallized layer after screen printing, thereby improving the quality and reliability of metal-ceramic sealing.

[0016] (2) The method of the present invention performs homogenization, degassing and activation treatment on the metallization paste, which can effectively improve the quality of the metallization paste and enhance the quality and reliability of metal-ceramic sealing. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is an enlarged physical picture of the ceramic material containing the metallization paste layer prepared in Example 1.

[0018] Figure 2 This is an enlarged physical picture of the ceramic material containing the metallized paste layer prepared in Comparative Example 1.

[0019] Figure 3 This is an enlarged physical picture of the ceramic material containing the metallized paste layer prepared in Comparative Example 2. DETAILED DESCRIPTION

[0020] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments. Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0021] The metallization paste used in the embodiments of the present invention was purchased from WINNER TECHNOLOGY Co., Ltd., model: WT-MMSM.

[0022] Example 1 (1) The metallized paste is homogenized by a homogenizer under vacuum conditions, wherein: the homogenization speed is 1300r / min, the homogenization time is 10min, and the vacuum degree is controlled to be -100KPa during homogenization, to obtain a homogenized metallized paste. The homogenized metallized paste is placed in an ultrasonic degassing machine for degassing, wherein: the ultrasonic frequency is 80KHz, and the degassing time is 10min, to obtain an activated metallized paste.

[0023] (2) The activated metallization paste is screen-printed twice on the ceramic surface to be sealed (the width of the ceramic surface to be sealed is 3 mm). The process parameters of the first screen printing are: ambient temperature of 22~26℃, humidity of 30~50%, screen mesh of 200 mesh, wire diameter of 30μm, screen spacing of 2mm, scraper angle of 60°, downward pressure stroke of 32μm, printing speed of 40mm / s, and screen printing thickness of 28μm. After the first screen printing, the screen-printed ceramic is placed in an oven and dried at 110℃ for 30min; then the second screen printing is carried out. The process parameters of the second screen printing are: ambient temperature of 22~26℃, humidity of 30~50%, screen mesh of 200 mesh, wire diameter of 30μm, screen spacing of 2mm, scraper angle of 60°, downward pressure stroke of 32μm, printing speed of 40mm / s, and screen printing thickness of 31μm. After the second screen printing, the ceramic after the second screen printing is placed in an oven and dried at 110° C. for 30 minutes. After drying, a ceramic material containing a metallized paste layer is obtained; wherein: the total thickness of the metallized paste layer is 59 μm.

[0024] (3) The ceramic material containing the metallization paste layer is placed in a metallization furnace and sintered at 1500° C. for 1 h to obtain a ceramic material containing a metallization layer. The thickness of the metallization layer is about 25 μm.

[0025] The actual picture of the ceramic material containing the metallized paste layer obtained in step (2) of this embodiment is as follows: Figure 1 As shown, it can be seen that the metallization paste layer has no defects such as cracks, grooves and pits.

[0026] Comparative Example 1 It is basically the same as Example 1, except that the screen printing process in step 2 is different, as follows: (2) The activated metallized paste is screen-printed once on the ceramic surface to be sealed (the width of the ceramic surface to be sealed is 3 mm). The process parameters of the first screen printing are as follows: the ambient temperature is 22-26°C, the humidity is 30-50%, the screen mesh is 100 mesh, the wire diameter is 40 μm, the screen spacing is 3 mm, the scraper angle is 60°, the downward stroke is 32 μm, the printing speed is 40 mm / s, and the screen printing thickness is 59 μm. After the first screen printing, the screen-printed ceramic is placed in an oven and dried at 110°C for 30 minutes to obtain a ceramic material containing a metallized paste layer; the total thickness of the metallized paste layer is 59 μm.

[0027] The actual picture of the ceramic material containing the metallized paste layer obtained in step (2) of this comparative example is as follows: Figure 2 As shown, it can be seen that there is an obvious groove in the middle of the metallization paste layer.

[0028] Comparative Example 2 The method is basically the same as Example 1, except that the activation process in step (1) is different, as follows: (1) The metallized paste was stirred at 25° C. and 300 r / min for 1 h using a slurry stirrer to obtain an activated metallized paste.

[0029] The actual picture of the ceramic material containing the metallized paste layer obtained in step (2) of this comparative example is as follows: Figure 3 As shown, it can be seen that obvious pits appear on the surface of the metallization paste layer.

[0030] Comparative Example 3 It is basically the same as Example 1, except that the screen printing process in step 2 is different, as follows: (2) The activated metallization paste is screen printed once on the ceramic surface to be sealed (the width of the ceramic surface to be sealed is 3 mm). The process parameters of the screen printing are as follows: the ambient temperature is 22-26°C, the humidity is 30-50%, the screen mesh is 200 mesh, the wire diameter is 30 μm, the screen spacing is 2 mm, the scraper angle is 60°, the downward stroke is 32 μm, the printing speed is 40 mm / s, and the screen printing thickness is 28 μm. There are no defects such as cracks, grooves and pits on the surface of the metallization paste layer.

[0031] The thickness of the metallization layer of the ceramic material containing the metallization layer prepared in this comparative example is about 12 μm.

[0032] Example 2 (1) The metallized paste is homogenized by a homogenizer under vacuum conditions, wherein: the homogenization speed is 1600r / min, the homogenization time is 10min, and the vacuum degree is controlled to be -90KPa during homogenization, to obtain a homogenized metallized paste. The homogenized metallized paste is placed in an ultrasonic degassing machine for degassing, wherein: the ultrasonic frequency is 80KHz, and the degassing time is 10min, to obtain an activated metallized paste.

[0033] (2) The activated metallization paste is screen-printed twice on the ceramic surface to be sealed (the width of the ceramic surface to be sealed is 4 mm). The process parameters of the first screen printing are: ambient temperature of 22-26°C, humidity of 30-50%, screen mesh of 165 mesh, wire diameter of 25 μm, screen spacing of 4 mm, scraper angle of 45°, press stroke of 35 μm, printing speed of 50 mm / s, and screen printing thickness of 32 μm. After the first screen printing, the screen-printed ceramic was placed in an oven and dried at 110°C for 30 minutes; then the second screen printing was performed, and the process parameters of the second screen printing were: the ambient temperature was 22~26°C, the humidity was 30~50%, the screen mesh number was 165 mesh, the wire diameter was 25μm, the screen spacing was 4mm, the scraper angle was 45°, the downward stroke was 35μm, the printing speed was 50mm / s, and the screen printing thickness was 38μm. After the second screen printing, the screen-printed ceramic was placed in an oven and dried at 110°C for 30 minutes. After drying, a ceramic material containing a metallized paste layer was obtained; wherein: the total thickness of the metallized paste layer was 70μm, and there were no defects such as cracks, grooves and pits on the surface of the metallized paste layer.

[0034] (3) The ceramic material containing the metallization paste layer is placed in a metallization furnace and sintered at 1400° C. for 1.5 h to obtain a ceramic material containing a metallization layer. The thickness of the metallization layer is about 29 μm.

[0035] Example 3 (1) The metallized paste is homogenized by a homogenizer under vacuum conditions, wherein: the homogenization speed is 1200r / min, the homogenization time is 12min, and the vacuum degree is controlled to be -90KPa during homogenization, to obtain a homogenized metallized paste. The homogenized metallized paste is placed in an ultrasonic degassing machine for degassing, wherein: the ultrasonic frequency is 40KHz, and the degassing time is 15min, to obtain an activated metallized paste.

[0036] (2) The activated metallization paste is screen-printed twice on the ceramic surface to be sealed (the width of the ceramic surface to be sealed is 4 mm). The process parameters of the first screen printing are: ambient temperature of 22-26°C, humidity of 30-50%, screen mesh of 300 mesh, wire diameter of 45 μm, screen spacing of 2 mm, scraper angle of 75°, downward stroke of 30 μm, printing speed of 30 mm / s, and screen printing thickness of 42 μm. After the first screen printing, the ceramic after screen printing is placed in an oven and dried at 130°C for 20 minutes; then the second screen printing is carried out, and the process parameters of the second screen printing are: the ambient temperature is 22~26°C, the humidity is 30~50%, the screen mesh is 300 mesh, the wire diameter is 45μm, the screen spacing is 2mm, the scraper angle is 75°, the downward stroke is 30μm, the printing speed is 30mm / s, and the screen printing thickness is 47μm. After the second screen printing, the ceramic after the second screen printing is placed in an oven and dried at 130°C for 20 minutes. After drying, a ceramic material containing a metallized paste layer is obtained; wherein: the total thickness of the metallized paste layer is 89μm, and there are no defects such as cracks, grooves and pits on the surface of the metallized paste layer.

[0037] (3) The ceramic material containing the metallization paste layer is placed in a metallization furnace and sintered at 1500° C. for 1 h to obtain a ceramic material containing a metallization layer. The thickness of the metallization layer is about 35 μm.

[0038] Example 4 (1) The metallized paste is homogenized by a homogenizer under vacuum conditions, wherein: the homogenization speed is 1500r / min, the homogenization time is 10min, and the vacuum degree is controlled to be -120KPa during homogenization, to obtain a homogenized metallized paste. The homogenized metallized paste is placed in an ultrasonic degassing machine for degassing, wherein: the ultrasonic frequency is 60KHz, and the degassing time is 12min, to obtain an activated metallized paste.

[0039] (2) The activated metallization paste is screen-printed twice on the ceramic surface to be sealed (the width of the ceramic surface to be sealed is 4 mm). The process parameters of the first screen printing are: ambient temperature of 22-26°C, humidity of 30-50%, screen mesh of 165 mesh, wire diameter of 35 μm, screen spacing of 2 mm, scraper angle of 45°, downward stroke of 30 μm, printing speed of 80 mm / s, and screen printing thickness of 30 μm. After the first screen printing, the screen-printed ceramics were placed in an oven and dried at 100°C for 40 minutes; then the second screen printing was performed, and the process parameters of the second screen printing were: the ambient temperature was 22~26°C, the humidity was 30~50%, the screen mesh number was 165 mesh, the wire diameter was 35μm, the screen spacing was 2mm, the scraper angle was 45°, the downward stroke was 30μm, the printing speed was 80mm / s, and the screen printing thickness was 32μm. After the second screen printing, the screen-printed ceramics were placed in an oven and dried at 100°C for 40 minutes. After drying, the third screen printing was performed according to the process parameters of the second screen printing. After printing, the ceramic material containing the metallized paste layer was dried at 100°C for 40 minutes to obtain a ceramic material; wherein: the total thickness of the metallized paste layer was 104μm, and there were no defects such as cracks, grooves and pits on the surface of the metallized paste layer.

[0040] (3) The ceramic material containing the metallization paste layer is placed in a metallization furnace and sintered at 1600° C. for 1 h to obtain a ceramic material containing a metallization layer. The thickness of the metallization layer is about 44 μm.

[0041] Performance Test: 1. Air tightness test and tensile test sample inspection: The metallized layers of the ceramic materials containing metallized layers prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were respectively electroplated with nickel, with a nickel layer thickness of 6 μm, and then placed in a hydrogen furnace and kept at 750°C for 1 hour for nickelization to obtain a ceramic material containing a nickel metal layer; the ceramic material containing a nickel metal layer was brazed with a 4J33 alloy gasket using oxygen-free copper at a brazing temperature of 1090°C for 15 minutes to obtain a test sample. The test samples were subjected to air tightness testing and tensile testing in accordance with industry standards SJ / T3326-2016 and SJ / T11583-2016, and the sealing air tightness was ≤ 1×10 -11 Pa·m 3 ·s -1 , tensile strength ≥90MPa is qualified. Test data are shown in Table 1.

[0042] 2. Thermal cycle performance test The metallized layers of the ceramic materials containing metallized layers prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were respectively electroplated with nickel, with a nickel layer thickness of 6 μm, and then placed in a hydrogen furnace and kept at 750°C for 1 hour for nickelization to obtain a ceramic material containing a nickel metal layer. The ceramic material containing a nickel metal layer was brazed with BNi-9 at a brazing temperature of 1070°C and kept warm for 4 minutes to obtain a test sample. The test sample was placed in a tubular furnace, heated from room temperature to 900°C in an air atmosphere, kept warm at 900°C for 1 hour, and then cooled to room temperature. The heating and cooling rate was ≥5°C / min, which was one cycle; the above steps were followed for periodic cyclic treatment, and the separation of ceramic and metal was observed. If the ceramic and metal were not separated within 80 cycles, it was qualified. The specific results are shown in Table 1.

[0043] Table 1 From the data in Table 1, it can be seen that the ceramic material containing the metallization layer prepared in Example 1 has good air tightness, tensile strength and thermal cycle performance after metal-ceramic sealing; the ceramic material containing the metallization layer prepared in Comparative Example 1 and Comparative Example 2 has poor air tightness, tensile strength and thermal cycle performance after metal-ceramic sealing. This shows that the thickness of each screen printing and the activation process of the metallization paste have a great influence on the performance of the metallization layer.

[0044] The ceramic material containing the metallization layer prepared in Comparative Example 3 has good airtightness when subjected to metal-ceramic sealing, but poor tensile strength and thermal cycle performance; this is mainly due to the fact that the thickness of the metallization layer is too thin.

[0045] In Examples 2 to 4, the preparation process parameters are mainly adjusted. After the prepared ceramic material containing the metallization layer is subjected to metal-ceramic sealing, the air tightness, tensile strength and thermal cycle performance will fluctuate to a certain extent, but all have good air tightness, tensile strength and thermal cycle performance.

[0046] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for screen printing a metallization paste, characterized in that: The following steps are involved: Step S1: homogenizing and degassing the metallized paste in sequence to obtain an activated metallized paste; Step S2: screen-printing the metallized paste activated in step S1 on the surface of the ceramic material to be sealed, controlling the thickness of each screen printing to be no more than 50 μm, and performing multiple screen printing to a set thickness to obtain a ceramic material containing a metallized paste layer; Step S3: sintering the ceramic material containing the metallization paste layer in step S2 to obtain a ceramic material containing the metallization layer.

2. The method for screen printing metallization paste according to claim 1, characterized in that: In step S1, the homogenization is performed under vacuum conditions, and the vacuum degree is -120~-90KPa.

3. The method for screen printing metallization paste according to claim 1 or 2, characterized in that: In step S1, the homogenization speed is 1200-1600 r / min, and the homogenization time is 10-15 min.

4. The method for screen printing metallization paste according to claim 1, characterized in that: In step S1, the degassing is performed by ultrasonic degassing.

5. The method for screen printing metallization paste according to claim 4, wherein the frequency of ultrasonic degassing is 40-80 kHz, and the time of ultrasonic degassing is 10-15 min.

6. The method for screen printing metallization paste according to claim 1, characterized in that: In step S2, the process parameters of screen printing include: screen mesh size of 80-350 mesh, wire diameter of 20-45 μm, screen spacing of 2-4 mm, scraper angle of 45-85°, downward pressure stroke of 28-35 μm, and printing speed of 30-100 mm / s.

7. The method for screen printing metallization paste according to claim 1 or 6, characterized in that: In the step S2, the thickness of each screen printing is controlled to be 25-50 μm.

8. The method for screen printing metallization paste according to claim 1, characterized in that: In the step S2, drying is performed after each screen printing; the drying temperature is 100-130°C.

9. The method for screen printing metallization paste according to claim 1, characterized in that: In the step S2, the thickness is set to 55-110 μm.

10. The method for screen printing metallization paste according to claim 1, characterized in that: In step S3, the sintering temperature is 1400-1500° C., and the sintering holding time is 0.5-1.5 h.

Citation Information

Patent Citations

  • Multi-level metalization on a ceramic substrate

    CN105074913A

  • Aluminum oxide ceramic production process

    CN110981549A

  • Metal heating film, ceramic heating body, preparation method and electronic atomization device

    CN114804925A

  • Coating preparation, for coating porcelain or ceramic ware

    DE19617147A1

  • Manufacturing method of holding device

    JP2020188043A